POSITION TRACKING CONTROL OF DC MOTOR FOR FRONT WHEEL SYSTEMS VIA HILS SIMULATION METHOD - Aili, M.F. A.; Ahmad, F.; Che Hasan, M.H.; Harun, M.H.; Harun, M.H. (Journal of Mechanical Engineering and Technology (JMET), 2023)
This paper present about position tracking control of DC motor to be used as the actuator controller for the front wheel test rig system. The controller strategy that was developed is based on Proportional-Integral-Derivative (PID) controller. It consists of one single closed control loops namely position tracking control loop. To evaluate the effectiveness of the proposed controller, simulation and experimental studies were performed by using various input demand such as saw tooth, sine and step functions in 5°, 10°, 15° and 20° with the present of steering ratio at 360:20. The results, it is found that the trend between simulation and experimental data are similar with the command position with acceptable level of error which less than 10% for application at hand.